Photorefractive keratectomy for patients with preoperative low Schirmer test value - Elham Tanbakouee; Mohammad Ghoreishi; Mohammad Aghazadeh-Amiri; Mehdi Tabatabaee; Mohadeseh Mohammadinia (Journal of Current Ophthalmology, 2016)
Purpose: To compare dry eye signs and symptoms between patients with preoperative low and normal Schirmer test after Photorefractive keratectomy (PRK). Methods: In this prospective, nonrandomized, comparative case series, 76 eyes of 76 patients were preoperatively categorized into two groups according to selected criteria for characterization of tear film status: the low Schirmer test value (STV) group and the normal STV group. For the tear function assessment, we performed a Schirmer test with and without anesthesia, tear break-up time (TBUT) test, and measurement dry eye symptoms using the Farsi translation of Ocular Surface Disease Index (OSDI) questionnaire pre- and 3 months post-operation. Results: Postoperatively, the Schirmer and TBUT values were significantly lower in both groups than preoperatively (all p < 0.05). Deterioration in tear secretion was significantly greater in the low STV group (p = 0.012), but tear stability was more compromised in the normal STV group (p = 0.021). The changes in OSDI score were not significant between the two groups. Conclusion: These results demonstrated that tear function deteriorates after PRK. Therefore, patients with low preoperative Schirmer test values should be thoroughly assessed for dry eye before proceeding with refractive surgery to eliminate postoperative complication.